Konsep masyarakat jaringan menurut manuel castells dan relevansinya pada masyarakat informasi - Baihaqi, Muhammad Ali (Maliki Interdisciplinary Journal, 2026)
The rapid development of information technology has transformed patterns of social, economic, and cultural interaction, giving rise to a new form of society centered on digital networks. This article examines Manuel Castells’ concept of the network society and its relevance to contemporary information society. Through a literature review of Castells’ works and related scholarly sources, this study identifies three fundamental elements that construct the network society: the space of flows, timeless time, and informational capitalism. These elements shape a decentralized, flexible social structure that relies heavily on technology. The analysis shows that Castells’ framework remains highly relevant in explaining current phenomena within the information society, such as the role of social media and digital communication platforms. In conclusion, the theory of the network society provides a comprehensive theoretical lens for understanding how information and technology evolve within modern society.